Nutritional impact of CFTR modulators in children with cystic fibrosis - Gaschignard, Margaux; Beaufils, Fabien; Lussac-Sorton, Florian; Gallet, Pauline; Clouzeau, Haude; Menard, Joris; Costanzo, Aurélie; Nouard, Lucie; Delhaes, Laurence; Tetard, Candice; Lamireau, Thierry; Fayon, Michael; et al. (Frontiers in Pediatrics, 2023)
Background Nutritional status is a major prognostic factor for breathing and the survival of patients with cystic fibrosis (CF). Since 2012, the development of CFTR modulators has considerably transformed the outcome of this disease. Indeed, both lung function and body mass index are improved by CFTR modulators, such as Lumacaftor/Ivacaftor. However, few data exist regarding the outcome of nutritional intakes under Lumacaftor/Ivacaftor. Methods We conducted a prospective single-center study in children with CF treated with Lumacaftor/Ivacaftor to evaluate their nutritional intake before and after treatment Results Thirty-four children were included in this study, with a median age of 12.4 years [11.9; 14.7]. There was no significant improvement in weight, height or BMI. Patients' total energy intake was not significantly changed with Lumacaftor/Ivacaftor, while carbohydrate intakes decreased significantly. We found that blood levels of vitamin E and Selenium were significantly increased under Lumacaftor/Ivacaftor, without a significant increase in supplementation. In patients with a BMI Z-score < 0 at treatment initiation, there was a significant improvement in weight and BMI Z-score, while TEI and carbohydrate intakes were significantly lower. Conclusion We showed that treatment with Lumacaftor/Ivacaftor improved the nutritional status of patients without necessarily being associated with an increase in nutritional intake. Although these data need to be confirmed in larger cohorts, they support the hypothesis that weight gain under modulators is multifactorial, and may be related to a decrease in energy expenditure or an improvement in absorption.